Sound over matter: Shaping architectural acoustics through 3D printing - Kempe, Markus (My University, 2025)
When tasked with designing a space for acoustic performances, shouldn’t the sound of that space be considered as carefully as its form? This question has been central to architectural acoustics since the early 1900s, when physicist Wallace Clement Sabine revolutionized the design of the Boston Music Hall through quantitative acoustic calculations, which led to the hall being one of North America’s most acoustically respected venues (Petersen et al., 1998). Today, acoustic considerations have spread to offices, museums, transport infrastructure, and even restaurants. But in many cases, the acoustic performance is rather expected to solve for the architectural vision, not to shape it. With exceptions such as Hamburg’s orchestra hall, the Elbphilharmonie, where architectural acoustic plays the primary role within its design. This thesis argues that with current technologies like acoustic simulation and robotic fabrication, we now have the tools to put the relationship between the acoustics and the architecture in better balance. Designing with acoustics in mind from the beginning could open new creative possibilities for architects. By integrating such intent early in the design process, this thesis suggests that sound and form can enhance one another and thereby benefit an overall spatial experience. To contextualize the findings, the thesis proposes an acoustic redesign of the building locally know as Palladium, a former cinema (now retail establishment) in central Gothenburg, Sweden. The intervention envisions how custom developed 3D-printed acoustic panels could transform such a venue, while simultaneously, reviving its original function towards an entertainment-focused program. The research traces a design process that includes spatially acoustic-oriented building interventions, exploration of three-dimensional surface patterns and how to robotically fabricate such geometries, to prototyping and site-specific applications of acoustic panels in the shape of diffusers and reflectors. Through computational design, acoustic analysis of three dimensional surface geometries and space, robotic fabrication and utilization of alternative sustainable materials, this thesis aims to contribute to the discourse on future technologies and -sustainability and performative architecture.
Keywords: Performative architecture, architectural acoustics, acoustic analysis, 3D printing, digital design, robotic fabrication